KAJIAN INFILTRASI BERBAGAI KELAS UMUR TEGAKAN POHON KARET (Hevea brasiliensis) DI SUB DAS BANYU IRANG DAS MALUKA - Yunisa Pratiwi; Syarifuddin Kadir; Muhammad Ruslan (Jurnal Sylva Scienteae, 2022)
This research aims to examine the characteristics of infiltration of various age classes of rubber tree stands (Hevea brasiliensis) and physical properties of soil. This research was carried out in the Banyu Irang sub-watershed of the Maluka Banjarbaru watershed, for 2 months. Determination of the location of infiltration was done by purposive sampling by using 3 replications in the 4 year, 8 year and 12 year age classes in the rubber tree stand, so that 9 replications were obtained. Infiltration measurements using a doubel ring infiltrometer, soil samples from the study site were then tested in the laboratory to determine the physical properties of the soil, namely soil texture, bulk density and porosity. The results of soil analysis on three age classes of rubber tree stands were obtained by clay and sandy clay. Has an average bulk density value in the 4 year, 8 year, 12 year age class of 1,57 gr/cm3, 1,31 gr/cm3 and 1,15 gr/cm3 and its porosity is 33,29 gr/cm3, 38,54 gr/cm3 and 44,17 gr/cm3. The infiltration capacity of 4, 8 and 12 years old is 96,906 mm/hour, 103,981 mm/hour and 104,651 mm/hour and the infiltration volume is 93,432 m3, 95,945 m3, 591 m3.Penelitian ini bertujuan untuk mengkaji karakteristik infiltrasi terhadap berbagai kelas umur tegakan pohon karet (Hevea brasiliensis) dan sifat fisik tanah. Penelitian ini dilaksanakan di Sub DAS Banyu Irang DAS Maluka Banjarbaru, selama 2 bulan. Penentuan lokasi infiltrasi dilakukan secara purposive sampling dengan menggunakan 3 kali ulangan di kelas umur 4 tahun, 8 tahun dan 12 tahun di tegakan pohon karet, sehingga diperoleh 9 kali ulangan. Pengukuran infiltrasi menggunakan alat doubel ring infiltrometer, sampel tanah dari lokasi penelitian kemudian dilakukan uji pada laboratorium untuk mengetahui sifat fisik tanah yaitu tekstur tanah, bulk density dan porositas. Hasil analisis tanah pada tiga kelas umur tegakan pohon karet diperoleh tekstur liat dan lempung liat berpasir. Memiliki rata-rata nilai bulk density pada kelas umur 4 tahun, 8 tahun, 12 tahun adalah sebesar 1,57 gr/cm3, 1,31 gr/cm3 dan 1,15 gr/cm3 dan porositasnya sebesar 33,29 gr/cm3, 38,54 gr/cm3 dan 44,17 gr/cm3. Kapasitas infiltrasinya dari umur 4, 8 dan 12 tahun 96,906 mm/jam, 103,981 mm/jam dan 104,651 mm/jam dan volume infiltrasi sebesar 93,432 m3,  95,945 m3, 591 m3.